IDENTIFIKASI KEMAMPUAN KOGNITIF SISWA BERDASARKAN GAYA BELAJAR DALAM MENYELESAIKAN SOAL-SOAL PADA POKOK BAHASAN IDENTITAS TRIGONOMETRI DI SMA NEGERI 4 JAYAPURA - Sirampun, Elsi; Agnes Teresa Panjaitan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics has a very important role in training students' cognitive abilities to think logically, systematically, and analytically. One of the topics in mathematics that requires a deep understanding is Trigonometry Identity. However, not all students have the same ability to solve trogonometry problems, because there are differences in learning styles that affect the way students understand and process information. In the context of Trigonometric Identity learning, these differences in learning styles can be a factor that affects students' cognitive abilities. This suggests that a uniform approach to learning is not always effective for all students. Therefore, it is important to identify students' cognitive abilities based on their learning styles, so that a more appropriate and effective learning model can be designed. Based on interviews with teachers at SMA Negeri 4 Jayapura, many students experienced difficulties in solving trigonometry problems. This can be caused by the incompatibility between the teaching model used and the student's learning style. By understanding students' cognitive abilities in the context of their learning styles, it is hoped that a more appropriate and effective learning model can be designed. This study aims to identify students' cognitive abilities based on learning styles in solving trigonometric identity subject problems. This research is a descriptive research using a qualitative approach. The data collection technique used learning style questionnaires, written tests and interviews. Based on the results of the research, the V14 Subjects have the cognitive ability to remember, understand, apply, analyze, evaluate, and create quite well. Subject A36, only has the cognitive ability to apply and evaluate. K43 subjects, only have the ability to understand, apply, and evaluate. The results of this research are expected to contribute to the development of a Differentiated Learning Model.